Efeito dos espectros de gota associados a diferentes arquiteturas de cultivares de soja no controle da ferrugem - Debortoli, Monica Paula (2011)
The efficiency of a fungicide is the result of the combination of a variety of factors including: time of application, environmental conditions, physiological condition of plant and application technology used. Already to the latter the proper the deposition and distribution of the active ingredient in the target is decisive for efficiency. The objective of this study was to evaluate the optimal droplet spectrum depending on the characteristics of plant architecture of soybean varieties. Two trails were conducted in the experimental area Phytus Institute in the city of Itaara, central region of Rio Grande do Sul in 2009/2010. The trial consisted of comparison of eight cultivars with different architectural characteristics of the plant with fungicide application using fine droplet spectrum. In Experiment 2, four cultivars were tested with application of fungicide using four spectra drops (very fine, fine, medium and coarse). To evaluate the effect of the treatments were assessed the following parameters: number of drops.cm-2, volume median diameter, Leaf Area Index, plant height, number of branches.plant-1, AUCPD, percentage of incident light in the canopy, yield soybean and yield components. The data of trial 1 showed that the architecture of plants (plant height, number of branches.plant-1 and LAI) significantly affected the deposition of droplets in the bottom and middle of the cultivars. It can also be inferred that the soybean cultivars are grouped due to their architectural characteristics allowing coverage similar drops. In trial 2, the application of fungicides with different droplet spectra allowed significant variations in disease control and on soybean yield. The fine droplet spectrum was more control and consistency in droplet deposition between the four cultivars.